Assessing stakeholder network engagement. (30th December 2020) - Okazaki, Shintaro; Plangger, Kirk; Roulet, Thomas; Menéndez, Héctor D.
Abstract : Purpose: With the popularity of social media platforms, firms have now tangible means not only to reach out to their stakeholders, but also to closely monitor those interactions. Yet, there are limited methodological advances on how to measure a firm's stakeholder networks, and the level of engagement firms have with these networks. Drawn upon the customer engagement and stakeholder theory literature, this study aims to propose an approach to calculate a firm's stakeholder network engagement (SNE) index. Design/methodology/approach: After deriving the SNE index formula mathematically, this study illustrates how the SNE index functions using eight firms' online corporate social responsibility (CSR) networks across four diverse industries. Findings: This study proposes and illustrates a new approach of capturing the SNE in a stakeholder network for use by academic and practical researchers. Research limitations/implications: Researchers can use the SNE index to assess engagement in stakeholder networks in various contexts. Practical implications: Managers can use the SNE index to assess, benchmark and improve the nature and quality of their CSR strategies to derive greater return on their CSR investments. Originality/value: Building on the stakeholder, communication and network analysis literatures, this study conceptualises SNE in four theoretical dimensions, namely, diffusion, accessibility, interactivity and influence. Then, an index that measures SNE is mathematically derived and empirically illustrated.